Assay of gastricsin and individual pepsins in human gastric juice. Issue 3 (March 1993) - Jones, A T; Balan, K K; Jenkins, S A; Sutton, R; Critchley, M; Roberts, N B
Abstract : AIMS: To develop and validate an analytical procedure for the quantitation of pepsins and gastricsin in human gastric juice and to assess its potential in a controlled gastric secretory study. METHODS: High performance ion-exchange chromatography was used to separate human pepsin 1, 3a, 3b, 3c and gastricsin from gastric juice. Computed chromatographic areas for each enzyme were quantified by relation to a known amount of a secondary standard porcine pepsin. The assay procedure was validated by recovery and analytical precision studies. Gastric secretions after pentagastrin and insulin stimulation from 10 patients with portal hypertension were used to assess the potential of the analytical procedure. RESULTS: The assay precision varied from 1.5 to 9.0% within batch and 7.5 to 18.1% between batch, with about 100% recoveries of porcine pepsin A from human gastric juice over the assay range 0.025-0.5 mg/ml. A fourfold increase in combined pepsin and gastricsin concentration was observed following pentagastrin and insulin stimulation. The mean percentage content of pepsins 3a, 3b, 3c, and 1 in non-stimulated gastric juice were 4%, 72%, 12% and 1.4%, respectively, and did not change significantly after gastric stimulation. An approximate doubling of the percentage of gastricsin (10% to 20%) relative to the pepsins was observed, however, after both insulin and pentagastrin stimulation. CONCLUSIONS: This procedure for quantifying individual human pepsins and gastricsin in gastric juice is simple and reliable. It may be of considerable importance in determining the mechanisms involved in the control and secretion of these digestive enzymes in man, including the effect of anti-ulcer drugs and our understanding of the pathophysiology of peptic ulcer disease.